Gender equitable policy reforms in Bangladesh: The role of informal networks and practices - Sultan, Maheen; Mahpara, Pragyna (Effective States and Inclusive Development Research Centre (ESID), 2022)
The paper explores how power operates in a gendered manner and how informal processes shape possibilities for gender equity. It investigates how and why gender equality policies are formulated, when these may not be popular with formal institutions, what role informal networks and practices play in their promotion or opposition, and whether the influence of informal networks varies across different types of policies. In clientelist contexts such as Bangladesh, informal networks and networking are particularly important, as they allow patrons to maintain their privilege, even after formal institutional reforms are carried out. (The paper analyses three types of policy or legal change cases: Compulsory Primary Education Act 1990 (ameliorative); Domestic Violence (DV) law 2010 (transformative status change policy); and the National Women’s Development Policy (NWDP) 2014 (transformative doctrinal change). These were placed on a continuum based on the degree of resistance they generate from actors resisting gender equality reforms using categories developed by Htun and Weldon (2018). Our analysis found that the degree of resistance in the compulsory primary education act was minimal, while transformative policy changes generated resistance with different outcomes. Though the three cases showed the importance of informal networks and practices, particularly personal relations, to gain access to key actors; their significance in diffusing resistance varied across cases. The ability of critical actors within the state depended on their ability to counter resistance from oppositional groups. Mobilization strategies that worked for law enactment did not necessarily work for policy implementation. The strength of informal networks used by the oppositional forces to gender equality and the political cost to the ruling party determined the effectiveness of informal networks across the cases. Currently, as Bangladesh politics shifts towards a more ‘dominant party’ system, the space for mobilization becomes limited for dissenting actors, particularly on issues where women’s rights groups disagree with the state.